2022
DOI: 10.3390/su14042229
|View full text |Cite
|
Sign up to set email alerts
|

Creating a Circular Design Workspace: Lessons Learned from Setting up a “Bio-Makerspace”

Abstract: In today’s industrial short-lived products, long-lasting materials are often implemented (e.g., oil-based plastics for throwaway packaging). Circular economy teaches the importance of keeping these materials in use, as well as designing end-of-lives that regenerate natural systems. Designers can help drive to a circular transition, but are they ready for this challenge? Educating young designers on circularity seems a fundamental first step, including knowing and meaningfully using circular, bio-based and biod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Following on this pathway did another research look into the necessary facilities to set-up a space in educational design workshops that allows for designing of, with and for nature, termed a 'bio-makerspace'. This study moreover highlights the accompanying barriers and enablers other institutions might encounter when installing a similar bio-makerspace [34].…”
Section: Figurementioning
confidence: 88%
See 1 more Smart Citation
“…Following on this pathway did another research look into the necessary facilities to set-up a space in educational design workshops that allows for designing of, with and for nature, termed a 'bio-makerspace'. This study moreover highlights the accompanying barriers and enablers other institutions might encounter when installing a similar bio-makerspace [34].…”
Section: Figurementioning
confidence: 88%
“…The knowledge, tools, and mindset changes brought about by these individuals' insights, design processes, and experience can hold significant value in spreading awareness about biodesign practices. Therefore, this still ongoing study is a natural consequence of the findings from stage one and previous peer research [26], [34].…”
Section: Stage 2 -How Are 'Biomaterials' Used Today and In Future Rea...mentioning
confidence: 91%
“…Second, empirical research about how makers innovate and what resources they use has mainly focused on non‐specialized makerspaces. At the same time, we can observe the phenomenon that research institutes, universities, and private companies establish more specialized makerspaces to foster user innovation in know‐how intense environments, such as biotechnology (Kera, 2012; Vuylsteke et al, 2022), healthcare (Svensson and Hartmann, 2018), physics (Fonda and Canessa, 2016), or quantum technologies (Ritter et al, 2021). Our study shows that specialized makerspaces can be complementary resource providers for hobby and professional innovators.…”
Section: Discussionmentioning
confidence: 99%
“…These selections can m actual purposes of the iterations. For example, the degree of sustainability and mental impact of the materials of the prototype can match the fidelity [52]; for i low-fidelity early prototypes can be made from recycled or repurposed materi thermore, such materials can match the purpose of the prototype [39,53] and its [14]; for instance, prototypes for a quick demonstration of an idea can be made purposed materials.…”
Section: The Role Of the Ideate Stage In Digital Fabrication Prototypingmentioning
confidence: 99%
“…A case study observed the effect of replacing traditional prototyping material in digital fabrication with biomaterial [13]. However, in experimental learning during the prototyping phase, the use of bio-based and biodegradable materials remains very limited [14].…”
Section: Introductionmentioning
confidence: 99%